2017
DOI: 10.1002/pds.4297
|View full text |Cite
|
Sign up to set email alerts
|

Good practices for real‐world data studies of treatment and/or comparative effectiveness: Recommendations from the joint ISPOR‐ISPE Special Task Force on real‐world evidence in health care decision making

Abstract: PurposeReal‐world evidence (RWE) includes data from retrospective or prospective observational studies and observational registries and provides insights beyond those addressed by randomized controlled trials. RWE studies aim to improve health care decision making.MethodsThe International Society for Pharmacoeconomics and Outcomes Research (ISPOR) and the International Society for Pharmacoepidemiology (ISPE) created a task force to make recommendations regarding good procedural practices that would enhance dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
284
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 312 publications
(302 citation statements)
references
References 40 publications
2
284
0
3
Order By: Relevance
“…Therefore, before pooling data through meta‐analysis (MA), validity remains a crucial aspect of study design and conception 25, 26, 27, 28. In particular, validation of the diagnoses is critical in the diabetes area, especially when in multinational epidemiological studies,29 because the lack of clinical data may compromise optimal algorithms for patients' and outcomes' identification.…”
Section: A Critical Appraisal Of Methodsological Issuesmentioning
confidence: 99%
“…Therefore, before pooling data through meta‐analysis (MA), validity remains a crucial aspect of study design and conception 25, 26, 27, 28. In particular, validation of the diagnoses is critical in the diabetes area, especially when in multinational epidemiological studies,29 because the lack of clinical data may compromise optimal algorithms for patients' and outcomes' identification.…”
Section: A Critical Appraisal Of Methodsological Issuesmentioning
confidence: 99%
“…This is addressed in detail in a companion paper led by ISPOR. 37 Because the initially planned research and the design and methodology underlying reported results may differ, it is also important to have transparency regarding what researchers actually did to obtain the reported results from a healthcare database study. This can be achieved with clear reporting on the detailed operational decisions made by investigators during implementation.…”
Section: Transparencymentioning
confidence: 99%
“…Real-world data refers to “data obtained outside the context of randomized controlled trials generated during routine clinical practice” (4). Electronic health records (EHRs) and insurance claims are perhaps the most common sources of real-world data used for health outcomes research and pragmatic clinical trials (4, 5). Compared to claims data, EHR data may have greater utility for identifying health outcomes due to the presence of richer clinical information including vital signs, laboratory test results, progress notes, discharge summaries, and radiologic and pathologic images and reports, among other information (6).…”
Section: Introductionmentioning
confidence: 99%